Could axillary lymph node dissection be omitted in the mastectomy patient with tumor positive sentinel node? - You, Ji Young; Lee, Eun Sook; Lim, Siew Kuan; Kwon, Youngmee; Jung, So-Youn (Frontiers in Oncology, 2023)
Background: Recent data from the ACOSOG Z0011 trial suggest that axillary lymph node dissection (ALND) may not be necessary for patients with positive sentinel lymph node biopsy (SLNB) receiving breast-conserving surgery (BCS) with irradiation. However, consensus statements and guidelines have recommended that patients undergoing mastectomy with tumor-positive sentinel node undergo completion ALND. In this study, we compared the locoregional recurrence rate of patients with tumor-positive sentinel nodes among three groups: mastectomy with SLNB, mastectomy with ALND and BCS with SLNB. Method: We identified 6,163 women with invasive breast cancer who underwent surgical resection at our institution between January 2000 and December 2011. Clinicopathologic data obtained from the prospectively collected medical database were analyzed retrospectively. Among the patients with sentinel node positive, mastectomy with SLNB was performed in 39 cases, mastectomy with ALND in 181 cases, and BCS with SLNB in 165 cases. The primary end point was the loco-regional recurrence rate. Results: Clinicopathologic characteristics were similar among the groups. There were no cases of loco-regional recurrence in the sentinel groups. At a median follow-up of 61.0 months (last follow-up May 2013), the loco-regional recurrence rate of each group was 0% for BCS with SLNB and mastectomy with SLNB only, and 1.7% for mastectomy with ALND (p=0.182). Conclusion: In our study, there was no significant difference in loco-regional recurrence rates between groups. This result lends weight to the argument that SLNB without ALND may be a reasonable management for selected patients with appropriate surgery and adjuvant systemic therapy.